2019
DOI: 10.1007/s42770-019-00118-x
|View full text |Cite
|
Sign up to set email alerts
|

Defining microbial biomarkers for risk of preterm labor

Abstract: Preterm birth remains the main contributor to early childhood mortality. The vaginal environment, including microbiota composition, might contribute to the risk of preterm delivery. Alterations in the vaginal microbial community structure might represent a risk factor for preterm birth. Here, we aimed to (a) investigate the association between preterm birth and the vaginal microbial community and (b) identify microbial biomarkers for risk of preterm birth. Microbial DNA was isolated from vaginal swabs in a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 63 publications
5
17
0
1
Order By: Relevance
“…The most common exclusion criteria of otherwise eligible studies were the lack of CST grouping of results (Supplementary Table S3 ). In the final selection of studies, seven were excluded because a lack of CST grouping 11 , 21 26 , all women receiving cervical cerclage 27 , sampling after signs of labor 28 , no information regarding preterm birth for current pregnancy 29 , only the use of polymerase chain reaction (PCR) instead of sequencing 30 or multiple CSTs assigned to each woman because of multiple sampling points 31 .…”
Section: Resultsmentioning
confidence: 99%
“…The most common exclusion criteria of otherwise eligible studies were the lack of CST grouping of results (Supplementary Table S3 ). In the final selection of studies, seven were excluded because a lack of CST grouping 11 , 21 26 , all women receiving cervical cerclage 27 , sampling after signs of labor 28 , no information regarding preterm birth for current pregnancy 29 , only the use of polymerase chain reaction (PCR) instead of sequencing 30 or multiple CSTs assigned to each woman because of multiple sampling points 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Também ajuda nisso o fato de o NGS ser completamente independente do cultivo, permitindo a identificação de microrganismos não cultiváveis, que representam mais de 90% da diversidade microbiana conhecida [23]. O conhecimento hoje já relaciona a microbiota com doenças e comorbidades humanas como Alzheimer [24], parto prematuro [25,26] e autismo [27], tratando o ser humano não mais como um organismo, mas como um "superorganismo" composto de células humanas e microbianas [28]. O mesmo também é válido para relações dos microrganismos com plantas [29] e com animais [30].…”
Section: Contribuições Do Ngsunclassified
“…In addition, the effect of the microbiome of pregnant women on the prognosis during pregnancy and PTB has been studied. [17][18][19][20][21] However, according to previous studies, the vaginal microbiome shows differences according to race and place of residence 16,22 , and a study has also reported that there is no relationship between PTB and a speci c microbiome in some races. 23 Ureaplasma spp., which is known to be associated with PTB, colonizes the vagina in women without any pregnancy complications.…”
Section: Introductionmentioning
confidence: 99%